Possíveis implicações epistemológicas do conceito de interação não-ordinária para a noção de sincronicidade de Jung - Nunes, Angela Maria de Souza (1989)
This theoretical study proposes, in the amplest sense, the notion of non fragmented totality as a referential for a 'vision of the world' and, consequently, for building up knowledge. For this purpose it becomes necessary to establish the perspectives of an epistemological redimensioning, objectivating the establishment of the fundaments that possibilitate a systemic theory of knowledge which is based on the notion of totality. In a narrower sense, this theory refers to the so-called 'nonordinary autogenic systems', that are special systems which objectivate becoming an alternative for the interpretation of human systems. In this connection, the objective is the orientation towards the synthesis of a special conception in order to dominate that which is 'alive', in detriment to a still physicalistic language that originated from the transference of the concepts of physical science to other fields of knowledge. Thus, the premise is that by conceptualizing the so-called 'nonordinary autogenic systems', they become applicable in the field of psychology - more specifically, with regard to the phenomena of the psyche. To reachthis objective, one must endeavor to exemplify the proceeding usefulness of the autogenic systems in psychology by means of the still incipient attempts to apply the notion of non ordinary interaction (the central focus of these systems) to- Jung's principle of synchronicity. To attain the above-mentioned objectives, the first part of the present work is limited to the study of the sources from which the Western world's knowledge has been built up, including an avaluation of contemporary science's epistemological tendencies, in order to properly postion the notion of totality. Contiguous to this proposal, the works of determined personalities, who are outstanding in the West's scenario of knowledge, should be researched in view of their recognizedly having orientated themselves according to the referential of totality.